The role of cadence on the VO2 slow component in cycling and running in triathletes - Billat, V. L.; Mille-Hamard, L.; Petit, B.; Koralsztein, J. P. (International Journal of Sports Medicine, 1999)
The purpose of this study was to compare the effect of two different types of cyclic severe exercise (running and cycling) on the VO2 slow component. Moreover we examined the influence of cadence of exercise (freely chosen [FF] vs. low frequency [LF]) on the hypothesis that: 1) a stride frequency lower than optimal and 2) a pedalling frequency lower than FF one could induce a larger and/or lower VO2 slow component. Eight triathletes ran and cycled to exhaustion at a work-rate corresponding to the lactate threshold + 50% of the difference between the work-rate associated with VO2max and the lactate threshold (delta 50) at a freely chosen (FF) and low frequency (LF: - 10 % of FF). The time to exhaustion was not significantly different for both types of exercises and both cadences (13 min 39 s, 15 min 43 s, 13 min 32 s, 15 min 05 s for running at FF and LF and cycling at FF and LF, respectively). The amplitude of the VO2 slow component (i.e. difference between VO2 at the last and the 3rd min of the exercise) was significantly smaller during running compared with cycling, but there was no effect of cadence. Consequently, there was no relationship between the magnitude of the VO2 slow component and the time to fatigue for a severe exercise (r = 0.20, p = 0.27). However, time to fatigue was inversely correlated with the blood lactate concentration for both modes of exercise and both cadences (r = - 0.42, p = 0.01). In summary, these data demonstrate that: 1) in subjects well trained for both cycling and running, the amplitude of the VO2 slow component at fatigue was larger in cycling and that it was not significantly influenced by cadence; 2) the VO2 slow component was not correlated with the time to fatigue. If the nature of the linkage between the VO2 slow component and the fatigue process remains unclear, the type of contraction regimen depending on exercise biomechanic characteristics seems to be determinant in the VO2 slow component phenomenon for a same level of training.